The Effectiveness Of Mass Marketing Communication As A Digital Logistics Tools In Promoting A New Online Public Service Platform - Ibrahim, Irwan; Ismail, Albert Feisal; Amer, Afizan; Md. Jani, Siti Hajar (ExcelingTech, 2019)
This paper aims to review a framework that investigate the effectiveness of mass marketing communication as a digital logistics tools toward promoting a new online public service platform "i-akaun" for Employees Provident Fund (EPF). The use of online public service platform by the government for participatory and interactive relationships is increasing today. More precisely, the descriptive nature of the study resides in its ability to explain how mass marketing communication as a digital logistics tools can promote the usage of new online service platform users regard the status performance of advertising, public relation and event as mass marketing as a digital logistics tools. A critical analysis of mass marketing communication as a digital logistics tool wheel shows it to be a checklist, a starting point in the examination on a set of mass marketing communication mix tool, but it is not as such of immense help to the decision maker and it was followed by a quantitative approach with a descriptive analysis was involve. Hence, the survey and observation are the methods that will used to collect the information and data. The analysis of communication gaps gives directions for formulating strategic decisions. In this framework, tactical decisions concern the components of the mass marketing communication as a digital logistics tools mix framework, activities, means and vehicles of communication.